2016
DOI: 10.1111/cge.12742
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia and severe muscle CoQ10 deficiency in a patient with a novel mutation in ADCK3

Abstract: Inherited ataxias are a group of heterogeneous disorders in children or adults but their genetic definition remains still undetermined in almost half of the patients. However, CoQ10 deficiency is a rare cause of cerebellar ataxia and ADCK3 is the most frequent gene associated with this defect. We herein report a 48 year old man, who presented with dysarthria and walking difficulties. Brain magnetic resonance imaging showed a marked cerebellar atrophy. Serum lactate was elevated. Tissues obtained by muscle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
5
45
1
Order By: Relevance
“…Compared with the patient reported previously , the patient described in this study exhibits fewer and milder symptoms. We speculate that this is most likely because of lesser severity of the patient's UQ deficiency, based on the comparison of quinone levels in skin fibroblasts derived from the patients as well as in vitro assessment of the functional impact of the patients' mutations (Figs A, B, and A).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Compared with the patient reported previously , the patient described in this study exhibits fewer and milder symptoms. We speculate that this is most likely because of lesser severity of the patient's UQ deficiency, based on the comparison of quinone levels in skin fibroblasts derived from the patients as well as in vitro assessment of the functional impact of the patients' mutations (Figs A, B, and A).…”
Section: Discussionsupporting
confidence: 90%
“…Fibroblasts of the previously reported COQ7 patient (V141E) were shown to exhibit severe UQ deficiency . However, the previous study did not report DMQ levels, which is a more sensitive and a more direct indication of reduced COQ7 enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, in contrast, we demonstrated that lack of COQ8A in mice results in a mild phenotype with progressive cerebellar ataxia, mild exercise intolerance, and moderate CoQ deficiency (Figure 6B), recapitulating the more frequent features of ARCA2 (Aure et al, 2004; Barca et al, 2016; Gerards et al, 2010; Horvath et al, 2012; Lagier-Tourenne et al, 2008; Mignot et al, 2013; Mollet et al, 2008). Thus, this work establishes Coq8a −/− mice as a valid model system for studying ARCA2 and testing potential treatments.…”
Section: Discussionmentioning
confidence: 70%